Eksekusi Jaminan Fidusia Setelah Adanya Keputusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 dan Nomor 2/PUU-XIX/2021 - Yoga Muslim Irmanda; Yunanto Yunanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Public interest in fiduciary guarantees is increasing and creates opportunities for several problems to occur, such as the execution of fiduciary guarantees when the debtor breach the contract. In the execution process, the creditors often done an arbitrary action that cause the debtor suffers a loss. The polemic over the execution of fiduciary guarantees has led to a judicial review of the Fiduciary Guarantee Law. From the judicial review, MK Decision Number 18/PUU-XVII/2019 and MK Decision Number 2/PUU-XIX/2021 were issued. On the other hand, the decision is considered to have caused a loss to the creditor. The law is expected to create justice and provide legal certainty to all people. The author uses a normative juridical method to further examine legal certainty for creditors regarding the existence of the Constitutional Court Decision Number 18/PUU-XVII/2019 and the Constitutional Court Decision Number 2/PUU-XIX/2021 in carrying out the execution of fiduciary guarantee objects. Execution of fiduciary guarantees must still be carried out by creditors in accordance with Law Number 42 of 1999 concerning Fiduciary Guarantees if they fulfill the conditions in the form of an agreement about a breach of contract and secondly, namely the fiduciary giver (debtor) voluntarily surrenders the fiduciary guarantee object in the context of execution. With the Constitutional Court's decision, it is hoped that the agreement between the creditor and the debtor will be made in more detail, especially on the point of default of the debtor.